Asuhan Kebidanan Komunitas Pada Keluarga Tn “Z” di Dusun Bangkang Desa Prabu Wilayah Kerja Puskesmas Kuta - Rina Heri Wistuti; Hulfa Ahadian Haryanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The purpose of the study was to obtain a real picture in providing community midwifery care in the context of the family to Mrs. M with Postpartum and Neonatal Physiology in Bangkang Hamlet, Prabu Village, Pujut District, Central Lombok Regency. After practicing community midwifery and implementing comprehensive community midwifery care, a good working relationship with Mr.